Indications and benefits of intraoperative esophagogastroduodenoscopy - Stašek, Martin; Aujeský, René; Vrba, Radek; Loveček, Martin; Chudáček, Josef; Janda, Petr; Gregořík, Michal; Vomáčková, Katherine; Neoral, Čestmír; Klos, Dušan (Wideochirurgia i inne techniki maloinwazyjne, 2018)
INTRODUCTION: Intraoperative esophagogastroduodenoscopy (IOG) is a diagnostic and therapeutic method for a variety of special conditions in upper gastrointestinal (UGI) pathology. The indication remains individual due to insufficient evidence and limited training of surgeons in digestive endoscopy. AIM: To evaluate the indications, benefits and risks of IOG. MATERIAL AND METHODS: A single-center retrospective study of 110 consecutive IOGs in 104 patients was performed. The preoperative plan, the timing of IOG, preoperative evaluation, intraoperative finding, localization of the pathology, type of the procedure, change of expected therapy and complications were assessed. RESULTS: The cohort comprised 29 esophageal tumors, 5 tumors of the cardia, 36 gastric tumors, gastrointestinal bleeding (8), esophageal diverticula (3), perforations (3), GERD (5), mediastinal pathology (3), fistula (4), assessment of nutrition (10), duodenal adenoma (2), ulcer disease, esophageal stenosis and gastric volvulus. The indication for IOG was established preoperatively in 79% and intraoperatively in 21%. The lesion was localized in 96.4%. The therapy was altered to a wider resection (11), smaller resection (5), localization and surgical therapy of bleeding (8) or allowed minimally invasive surgery (25). A total of 3 postoperative complications included gastric perforation and positivity of resection line (following EMR/ESD) and recurrent bleeding. The 30-day mortality reached 3.6% without a specific cause in IOG. CONCLUSIONS: The IOG is a complementary method in the diagnosis and treatment of UGI pathology. It enables minimally invasive finalization of the procedures and individualization of the therapy.
Keywords: laparoscopic endoscopic cooperative surgery; gastric and esophageal tumors; intraoperative upper endoscopy